Neurology and Modernist Literature. Issue 4 (April 2014) - Christensen, Susie
Abstract In recent years, there has been a surge in work by literary critics which considers the literature of the late‐nineteenth and early‐twentieth centuries in relation to neurology. This builds upon an already substantial body of work which has studied the literature of this period in relation to psychology or psychoanalysis. The work of medical historians is crucial for literary critics seeking to tease out the complex relationship between psychology and neurology in this period and also in establishing that psychology must form a central aspect of historically grounded studies of neurology and literature which focus on the late‐nineteenth and early‐twentieth centuries. Focusing on neurology and psychology alongside one another in relation to modernist literature demands a new account of Freud and Freudianism. Neurology also needs to be seen as a key element of embodiment in modernist literature. The first part of the article explores these issues. The second part considers recent work by literary critics on neurology and literature and is split into two sections. The first surveys recent work which gives a historically grounded account of neurology and modernist literature, touching on work which considers authors such as Samuel Beckett and Virginia Woolf. The second section focuses on works which examine modernist literature in relation to the neurology and/or neuroscience of today, questioning the efficacy of such an approach.